2022
DOI: 10.1093/pubmed/fdac027
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of multiple combined lifestyle interventions in reducing blood pressure among patients with prehypertension and hypertension: a network meta-analysis

Abstract: Background Different combinations of lifestyle interventions have been studied with varying results on hypertension control. Hence, this review was done to compare multiple combined lifestyle intervention in reducing blood pressure (BP) among patients with prehypertension or hypertension. Methods We conducted systematic search in the following databases: MEDLINE, PubMed Central, CENTRAL, ScienceDirect, Google Scholar from 196… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Previous meta-analysis is consistent with our results; it showed that healthy diet and physical activity are the best combination for lowering blood pressure and exhibit the highest reduction of blood pressure (SBP −9.88 mmHg and DBP −6.28 mmHg) compared to other intervention models. 59 Our result provides a strong scientific base for implementing the "balance of diet and exercise" concept in China, which is the second core recommendation among the Dietary Guidelines for Chinese Residents (2022). This study has several strengths.…”
Section: Food and Function Papermentioning
confidence: 82%
“…Previous meta-analysis is consistent with our results; it showed that healthy diet and physical activity are the best combination for lowering blood pressure and exhibit the highest reduction of blood pressure (SBP −9.88 mmHg and DBP −6.28 mmHg) compared to other intervention models. 59 Our result provides a strong scientific base for implementing the "balance of diet and exercise" concept in China, which is the second core recommendation among the Dietary Guidelines for Chinese Residents (2022). This study has several strengths.…”
Section: Food and Function Papermentioning
confidence: 82%
“…Secondly, based on the CCR/WC ratio, clinicians can personalize treatment plans more effectively. For hypertensive individuals with higher CCR/WC ratios, a greater emphasis on managing muscle mass and abdominal obesity, possibly through tailored dietary and exercise programs, may be warranted to control hypertension ( 48 ). Lastly, the findings of this study bear importance in shaping public health policies.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, the risk of premature death from NCDs is 22%. (3) Obesity, increased blood glucose, high BP, high cholesterol levels, physical inactivity, alcohol consumption, and smoking are the major risk factors for NCDs (4)(5)(6)(7)(8)(9)(10). Nepal has a particularly high prevalence of certain NCD risk factors, such as current smoking, low fruit and vegetable consumption, increased blood pressure, and abnormal lipid levels.…”
Section: Introductionmentioning
confidence: 99%